Randomized clinical study comparing metallic and glass fiber post in restoration of endodontically treated teeth (2014)
Background: Post-retained crowns are indicated for endodontically treated teeth (ETT) with severely damaged coronal tissue. Metallic custom and prefabricated posts have been used over the years, however, due to unacceptable color, extreme rigidity and corrosion, fiber posts, which are flexible, aesthetically pleasing and have modulus of elasticity comparable with dentin were introduced. Aim: To compare clinical performance of metallic and glass fiber posts in restoration of ETT. Materials and Methods: 40 ETT requiring post retained restorations were included. These teeth were randomly allocated into 2 groups. Twenty teeth were restored using a glass fiber-reinforced post (FRP) and 20 others received stainless steel parapost (PP), each in combination with composite core buildups. Patients were observed at 1 and 6 months after post placement and cementation of porcelain fused to metal (PFM) crown. Marginal gap consideration, post retention, post fracture, root fracture, crown fracture, crown documentation and loss of restoration were part of the data recorded. All teeth were assessed clinically and radio-graphically. Fisher’s exact test was used for categorical values while log-rank test was used for descriptive statistical analysis. Results: One tooth in the PP group failed, secondary to documentation of the PFM crown giving a 2.5% overall failure while none in the FRP group failed. The survival rate of FRP was thus 100% while it was 97.5% in the PP group. This however was not statistically significant (log-rank test, P = 0.32). Conclusion: Glass FRPs performed better than the metallic post based on short-term clinical performance.